The Asset Capital-based Adaptation of the Marginalized People in the Northeast of Thailand Amid the Covid -19 Pandemic - Prabnok, Puttharak; Chamaratana, Thanapauge; Meekaew, Nattapon; Phatchaney, Kritsada; Jearviriyaboonya, Jakkrich (Journal of Ecohumanism, 2024)
This study aimed to investigate the capital assets- based adaptation of marginalized people in the Northeastern Thailand amid the Covid-19 pandemic. This study employed a qualitative research methodology to collect data through interview approaches. The results revealed that the majority of the marginalized people in northeastern Thailand adapted capital assets through the support of family members, especially children who have skills in communication technology to access health-related information and assistance from government and private agencies. Additionally, social capital was also used to help people in the community. This resulted in the communities with high-performance leaders being able to deal with the problem during the Covid- 19 pandemic effectively. Furthermore, the assistance of outsiders was another way for the adaptation since the marginalized people barely use financial and physical capital due to accessibility and capital limitations.